Second reported outbreak of pneumococcal pneumonia among shipyard employees in Turku, Finland, August–October 2023: a case–control study - Kitowska, Wioleta; Gonzalez-Perez, Ana Cristina; Sequeira, Neto Joana; Kanerva, Mari; Kaukavuori, Heikki; Lindström, Irmeli; Frilander, Heikki; Dub, Timothée; Siira, Lotta; Pneumococcal Shipyard Outbreak Team (Cambridge University Press (CUP), 2026)
In August 2023, the Finnish Institute for Health and Welfare received reports of a potential cluster of pneumococcal pneumonia cases among shipyard employees in Turku, Finland. Considering a similar outbreak in the same shipyard in 2019, we initiated a case-control study to investigate individual and environmental risk factors specific to this occupational setting in order to inform targeted prevention measures. In total, 14 hospitalized cases were identified from 19 August to 15 October 2023. Streptococcus pneumoniae serotypes 4 and 9 V were isolated from blood cultures of seven cases. Eleven cases and 67 controls working at the shipyard were included in the case-control study. Compared with controls, cases were more likely to be living in an apartment/studio or a hotel/hostel, and less likely in a house or with family. Furthermore, cases were more likely to have a shorter duration of employment (< 1 year) at the shipyard compared to controls. Control measures, including an information and a vaccination campaign, were implemented. We emphasize shipyard-wide hygiene improvements and recommend nationwide consideration of expanding pneumococcal vaccination eligibility to all shipyard construction employees as an occupational high-risk group.